2011
DOI: 10.1002/ibd.21584
|View full text |Cite
|
Sign up to set email alerts
|

Supplemental antioxidants do not ameliorate colitis development in HLA-B27 transgenic rats despite extremely low glutathione levels in colonic mucosa5

Abstract: Antioxidant supplementation was ineffective in HLA-B27 rats despite low mucosal glutathione levels, because colitis development did not coincide with oxidative stress in this model. This indicates that the neutrophilic respiratory burst, and thus innate immune defense, is compromised in HLA-B27 rats. As supplementation with both calcium and antioxidants attenuated colitis development, we speculate that this protective effect is attributed to calcium only.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 39 publications
0
8
2
Order By: Relevance
“…These rats revealed several features that are also found in human IBD, such as reduced body weight, diarrhea, increased expression of proinflammatory genes such as COX-2, iNOS, TNFα, and IL1β in the colon mucosa, MPO activity, intestinal mucosal inflammation, and injury. In contrast, as demonstrated by other researchers [29], the development of colitis in HLA-B27 was not associated with an increase in oxidative DNA damage.…”
Section: Discussioncontrasting
confidence: 51%
“…These rats revealed several features that are also found in human IBD, such as reduced body weight, diarrhea, increased expression of proinflammatory genes such as COX-2, iNOS, TNFα, and IL1β in the colon mucosa, MPO activity, intestinal mucosal inflammation, and injury. In contrast, as demonstrated by other researchers [29], the development of colitis in HLA-B27 was not associated with an increase in oxidative DNA damage.…”
Section: Discussioncontrasting
confidence: 51%
“…α-Tocopherol was utilized alone [47] and in combination with other nutrients [209] , [210] . Interestingly, the results had shown an absence of colonic antioxidant effect, when vitamin E was utilized with vitamin C and GSH [210] .…”
Section: Resultsmentioning
confidence: 99%
“…α-Tocopherol was utilized alone [47] and in combination with other nutrients [209] , [210] . Interestingly, the results had shown an absence of colonic antioxidant effect, when vitamin E was utilized with vitamin C and GSH [210] . Some meta-analyses have shown that antioxidant supplements do not result in the presumed health benefit, but paradoxically a high intake of antioxidants is associated with increased mortality [211] , [212] .…”
Section: Resultsmentioning
confidence: 99%
“…Decreased disease manifestations by N-acetylcysteine support this contention [129, 130]. However, the jury is still out on the causal role of mucosal GSH/GSSG disruption in IBD pathogenesis since antioxidant therapies with vitamin C, E, and GSH were without effect in the HLA-B27 transgenic rat model of IBD [131]. …”
Section: Intestinal Oxidative Stress and Gut Pathobiologymentioning
confidence: 99%